A critical study on the role of islamic criminal law and deterrence of crimes in Malaysia / Ravindhran Kutty Krishnan - Ravindhran Kutty, Krishnan (2009)

(untitled)
This study combines an evaluation of both criminological explanation of crimes in Malaysia and the extent in which regular and Islamic penal laws are effective in reducing spiralling crime rates in this country. The scope of research encompasses a study on three segments of criminal offences including _property (robbery), murder and rape (sexual) offences. Largely based on Shaw and Mc Kay's work, this study examines the extent in which crimes are caused by extensive social disorganisations. rl The findings of the study critically postulated that property offences are largely ;§ influenced by poverty and unemployment and it appears that tougher sentencing such as the implication of Islamic penal codes are effective deterrent to this crime. However, there is less evidence showing the same to rape and murder offences where unlike property crimes that are considered 'calculated crimes' these crimes are mostly caused by emotional and psychological impairments. The study showed heavier punitive measures was not effective towards these types of crimes as they are considered as crimes of passion where offenders committed the offences in a state of mind that is emotionally or psychologically foiled.